2019
DOI: 10.1002/app.47929
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable cellular poly(vinylidene) ferroelectrets: Optimization of CO2 driven inflation process

Abstract: Electrically charged cellular ferroelectrets can show excellent thermally stable piezoelectric activity and are therefore progressively used in electrochemical transducers. Given that an optimized cellular structure is a key for improving charge density and the associated piezoelectric properties in this material, we investigated the influence of CO2 inflation treatment using various gas diffusion expansion or inflation procedures on the piezoelectric d33 coefficient and thermal stability of cellular poly(viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Also, they showed that the highest d 33 (from 137 to 251 pC N À1 ) was generated when there was increase in the inflation pressure (from 3 to 5 MPa) at 130 °C constant temperature for a certain time. [107] More recently, Xu et al [108] fabricated a foamed PVDF/ multiwalled carbon nanotube (MWCNT) piezonanocomposite. The foam layer was created by the bead foaming technology utilizing supercritical carbon dioxide (scCO 2 ).…”
Section: -170mentioning
confidence: 99%
See 3 more Smart Citations
“…Also, they showed that the highest d 33 (from 137 to 251 pC N À1 ) was generated when there was increase in the inflation pressure (from 3 to 5 MPa) at 130 °C constant temperature for a certain time. [107] More recently, Xu et al [108] fabricated a foamed PVDF/ multiwalled carbon nanotube (MWCNT) piezonanocomposite. The foam layer was created by the bead foaming technology utilizing supercritical carbon dioxide (scCO 2 ).…”
Section: -170mentioning
confidence: 99%
“…Recently, Jahan et al [ 107 ] produced cellular PVDF–montmorillonite (MMT)–CaCO 3 ‐based piezoelectret films involving uniaxially stretched, GDE treated, and corona charged. Recently, Jahan et al [ 107 ] produced cellular PVDF‐montmorillonite (MMT) ‐CaCO 3 ‐based piezoelectret films involving uniaxial stretching, GDE treatment, and corona charging.…”
Section: Types Of Polymeric Piezoelectric Foamsmentioning
confidence: 99%
See 2 more Smart Citations